As relações dos Temas Transversais com base nos Objetivos de Desenvolvimento Sustentável e a saúde de participantes de um projeto social em Araraquara - Gomes, Vinícius de Sousa (Universidade Federal de São Carlos, 2025)
This research aims to explore how the learning of cross-cutting themes can contribute to the health of participants in a social basketball project. Using a qualitative approach, the study was conducted at the ASPA Institute, in Araraquara/SP, with children aged 7 to 10 years, through a pedagogical intervention consisting of six cross-cutting activities distributed across three thematic blocks. Data collection included semi-structured interviews with the participants of the local unit, the coordinator of the Multidisciplinary Department, and the reference Physical Education teacher of the social project, as well as field notes and documental analysis of the Institute’s Bylaws and Reference Guide. Data were analyzed using Structural Content Analysis (ANCO), based on isotopies, in order to identify recurring meanings in the participants’ statements and experiences. The theoretical framework is grounded in Jorge Larrosa-Bondía’s notion of experience, articulated with the health concepts from the Ottawa Charter (1986) and the 8th National Health Conference (1986). The results indicate that the implementation of cross-cutting themes within the context of educational sport is related to the health of children participating in the social project, strengthening bonds and expanding learning beyond the court, not limited to the biological dimension alone. The study contributes to the health debate by discussing the role of educational sport in promoting the health of children in situations of social vulnerability, reinforcing the importance of an interdisciplinary approach in Physical Education.
The relationships of Cross-Cutting Themes based on Sustainable Development Goals and the health of participants in a social project in Araraquara/SP
Keywords: Educação Física; Saúde; ODS; Temas Transversais; Esporte Educacional; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; 3. Saúde e Bem-Estar